AN INVESTIGATION OF THE RELATIONSHIP BETWEEN LABORATORY USE SKILLS OF GRADE 10 PHYSICAL SCIENCES LEARNERS AND THEIR ACADEMIC PERFORMANCE - Nhlapo, Sibongile; Bhagwandeen , Ritu; Lekhu, Motshidisi (International Online Journal of Education and Teaching, 2025)
Laboratory use skills, including basic and integrated science process skills, are taught in school science laboratories. This study aimed to investigate the relationship between grade 10 physical sciences learners' laboratory use skills and their academic performance. Four schools from the Lejweleputswa Educational District were randomly selected. A mixed methods approach was used, involving focus group interviews with seven teachers and a Likert-type questionnaire for 187 learners. The findings revealed a significant relationship between laboratory use skills and academic performance. Practical investigations are important in teaching physical sciences, despite challenges such as a lack of resources, functional laboratories, time, discipline, and novice teacher experience. Recommendations include workshops for novice teachers, mobile laboratories, integrating practical work into university curricula, compulsory Wi-Fi at schools, and monitoring by Departmental Heads. These findings impact teacher training, curriculum development, resource allocation, the connection between theory and practice, learners' academic success, and future career paths in science-related fields